PEMETAAN PENGARUH PERKEMBANGAN PASAR WAGE KOTA PURWOKERTO TERHADAP LINGKUNGAN PERMUKIMAN SEKITAR - Tantio Kartiko Pamulih; Widjonarko Widjonarko (Department of Urban and Regional Planning, Diponegoro University, 2014)
Fire accident that occurred in Pasar Wage (Wage Marketplace) in 2002 had forced the Government of Banyumas District (Kabupaten) to renovate and expand the area of Pasar Wage. Now, Pasar Wage has two floors, and it raises the new issue. Traders do not want to open their stalls on the 2nd floor due to their perception that “no merchandise are sold as good as on the 1st floor”. So, instead of using their second-floor stalls, many traders open their stalls on the pedestrian pathways. It certainly causes problems to the traffic and pedestrian activities. This research uses a spatial approach. Data collection has been done through mapping GIS analysis, visual observation, questionnaire distribution, and interview. The results show several impacts of Pasar Wage on its surrounding housing area. First, the impact on the land use with the emergence of commercial and mixed-use buildings replacing part of the housing area. The second impact is the increase of business and job opportunities for the local residents such as on-street parking, street vendors, and retail businesses. The trading activity in the pedestrians of Pasar Wage also induces traffic congestion in peak hours, especially near the east entrance of the marketplace. Last, it affects the condition of the physical environment such as the inundation and bad scent due to the clogged drainage or sewerage system. Therefore, government and community efforts are needed to overcome or minimize the negative impacts.